IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) KURIKULUM 2013 UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS SISWA PADA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL KELAS VIII.8 SMP NEGERI 21 BATAM - Indrawati Indrawati (MEDIA DIDAKTIKA, 2023)
The purpose of this study is to improve student learning outcomes and activities in the implementation of the 2013 curriculum Problem Based Learning (PBL) Learning Model in grade VIII.8. The author conducted research at SMP Negeri 21 Batam grade VIII.8 Mathematics subject for the 2020/2021 academic year. This Classroom Action Research uses qualitative Descriptive Techniques in two learning cycles through observation and tests of the ability to solve SPLDV problems Mastery of the Two Variable Linear Equation System material in grade VIII.8 SMP Negeri 21 Batam shows an increase, this can be shown by the average daily test results, but in cycle 1 (before using the PBL model) which is 63 and 69 and after using the PBL model to 70 in the cycle, While in cycle 2 it becomes 78. Based on the study of theory and frame of mind proposed by researchers, as well as the results of research conducted on grade VIII.8 students, it can be concluded that the Problem Base Learning (PBL) Learning Model can improve learning outcomes and student activeness in class during learning. Based on observations, student activities in implementing the PBL learning model have increased, namely the good category. In the initial data of activity observations of 50% sufficient quality, in cycle 1 it rose to 54% sufficient quality, and for cycle 2 it increased but not significantly by 67%.